TINGKAT PENGETAHUAN PETANI PADI SAWAH TERHADAP INOVASI TRANSPLANTER DI KELOMPOK TANI SINAR KENCANA II KAMPUNG BUMI KENCANA - Inara Angsi Prastisi; Indah Listiana; Helvi Yanfika; Serly Silviyanti S (Politeknik Negeri Lampung., 2023)
Sinar Kencana II Farmers Group is a farmer group that received transplanter machine assistance, but the majority of farmers still carry out the conventional rice planting process, only 20% of farmers have used transplanters. Farmers are still reluctant to use and apply transplanter machines on their farms because of limited knowledge and information about the use of these tools. This study aims to determine the level of knowledge of lowland rice farmers and the factors associated with the level of knowledge of farmers to transplanter innovation. This research was conducted at the Sinar Kencana Farmer Group II Kampung Bumi Kencana, Seputih Agung District, Central Lampung Regency. The data in this study were taken in October-November 2021. Determination of the number of samples using purposive sampling technique for all members who are members of the Sinar Kencana II farmer group as many as 62 respondents. The types of data taken are primary data and secondary data. Methods of data collection is done by observation, interviews and documentation. This study used census method and the data were analyzed descriptively with a quantitative approach and correlation analysis to see the factors related to the level of knowledge of farmers. The results showed that the level of knowledge of lowland rice farmers to transplanter innovation was generally in the high category with a score of 45,16%, knowledge of how to use transplanters was in the medium category with a score of 35,48%, and knowledge about the benefits of transplanters was in the high category with a score of 41,94%. The variables of formal education, non-formal education, and sources of information have a relationship or correlate with the level of knowledge of lowland rice farmers on transplanter innovation, while the variables of age and length of farming have no relationship with the level of knowledge of lowland rice farmers on transplanter innovation. Keywords: innovation, knowledge, transplanter